Phenotypic characterization of B cells and serum cytokine responses during Tuberculosis and Type 2 Diabetes - Shabangu, Ayanda Noncedo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.